AB0558 Accelerated infusion rates of RITUXIMAB is well-tolerated and safe in rheumatology practice: A single center experience. (23rd January 2014) - Can, M.; Alibaz-Öner, F.; Öner, S.; Atagunduz, P.; Inanc, N.; Direskeneli, H.
Abstract : Background: Rituximab (RTX), a chimeric monoclonal antibody which selectively targets CD20 positive B cells has been approved for the treatment of RA and other autoimmune diseases. Due to the possible risk of infusion reactions, a slow infusion rate (total infusion time: 255 min) is usually preferred. However, especially in oncology field, accelerated infusion of RTX is reported to be well-tolerated and safe (Ref 1). Objectives: The aim of our study was to evaluate whether accelerated infusion-rates of RTX would similarly be safe and tolerable in RA patients and other off-label indications. Methods: All patients treated with RTX for RA and other autoimune diseases between May 2011-January 2012 were recruited to the study. Each treatment course consisted of 2 RTX 1000 mg infusions-2 weeks apart. Total time of the infusion for the first cycle was 255 min. Second and subsequent infusions were administered over 120 min as follows: 0-30 min: 100 mg, 30-60 min: 200 mg, 60-90 min: 300 mg and 90-120 min: 400 mg. Methyl-prednisolone 100 mg IV, acetaminophen 1000 mg PO and diphenhydramine 50 mg IV were administered as premedications. The Clinical Trials Classification of Adverse Events (CTCAE) version 4.3 was used to categories side effects (Ref 2). Results: The study population comprised of 67 patients, 59 with RA (F/M: 53/6, mean age: 52.8 years), 4 sistemic lupus erythematosus (SLE), 1 lenfoma and three vasculitis patients. 61 fast infusions were administered: 2 patients had taken 4 times, 4 patients 3 times, 12 patients 2 times and 17 patients had taken at least one infusion. Seventeen patients (25.4%) had taken fast-infusion at the first course. Five categories of adverse events (AE) were identified: allergic reactions/skin itching, rhinitis, dyspnea/cough, pharyngeal disconfort/dysphagia, and other (vertigo, hypotension) according to CTCAE guide. A total of 8 patients experienced at least one AE. Six patients had a reaction on the first infusion (IRR), 1 patient on the second infusion and 1 patient on both infusions. Four patients complained of pharyngeal discomfort and dysphagia, 3 patients suffered from vertigo and hypotension and 1 patient complained about dyspnea and cough. When graded from 1 to 5 accoding to CTCAE v.4.3, Grade 1 IRRs were observed in a total of 5 patients and grade 2 IRR in 3 patients. Conclusions: In this study of fast infusions, adverse events after RTX were mostly mild and seems to be well-tolerated. Faster rituximab infusion times seem to be safe and might be incorporated into routine practice. References: Provencio M, Cerdeira S, Bonilla F, Sánchez A, España P. Rapid-infusion rituximab in lymphoma treatment. Ann Oncol. 2006 Jun;17(6):1027-8. Lacouture ME, Maitland ML, Segaert S, Setser A, Baran R, Fox LP, Epstein JB, Barasch A, Einhorn L, Wagner L, West DP, Rapoport BL, Kris MG, Basch E, Eaby B, Kurtin S, Olsen EA, Chen A, Dancey JE, Trotti A. A proposed EGFR inhibitor dermatologic adverse event-specific grading scale from the MASCC skin toxicity study group. Support Care Cancer. 2010 Apr;18(4):509-22 Disclosure of Interest: None Declared